2014
DOI: 10.1371/journal.pone.0090029
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Real Time Allele Specific Locked Nucleic Acid Quantitative PCR for Detection of HBV YIDD (ATT) Mutation and Evaluation of Its Application

Abstract: BackgroundLong-term use of nucleos(t)ide analogues can increase risk of HBV drug-resistance mutations. The rtM204I (ATT coding for isoleucine) is one of the most important resistance mutation sites. Establishing a simple, rapid, reliable and highly sensitive assay to detect the resistant mutants as early as possible is of great clinical significance.MethodsRecombinant plasmids for HBV YMDD (tyrosine-methionine-aspartate-aspartate) and YIDD (tyrosine-isoleucine-aspartate-aspartate) were constructed by TA clonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The range of application of qPCR is immense, such as measuring mRNA expression levels, DNA copy number, transgene copy number and expression analysis, allelic discrimination and measuring viral titers, etc. [ 5 , 6 , 7 , 8 ]. Thus, it has become the gold standard for accurate, sensitive and rapid quantification of gene expression [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The range of application of qPCR is immense, such as measuring mRNA expression levels, DNA copy number, transgene copy number and expression analysis, allelic discrimination and measuring viral titers, etc. [ 5 , 6 , 7 , 8 ]. Thus, it has become the gold standard for accurate, sensitive and rapid quantification of gene expression [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that CVR rate to antiviral therapy was significantly lower in patients infected with spontaneous rtM204I variants. Indeed, rtM204I variants are the predominant mutations causing resistance to NAs with low genetic barriers, such as LAM, L-dT, and CLV[6,24]. These variants can also reduce the susceptibility to entecavir therapy and induce entecavir resistance[25].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it is characterized by a dynamic stepwise process. Under the dual pressures of nucleoside analogues and host immunity, in some patients the HBV population gradually changes from wild to mutant strains and the mutant strains may even fully replace all the wild strains to become the predominant population (Zeng et al, 2014). As a consequence, the switch reduces the sensitivity of HBV to nucleoside analogues and finally confers clinical resistance.…”
Section: Introductionmentioning
confidence: 99%